The Emerging Mind - Ramchandran , Vilayanur; Mittal, A.K. (Gyan Management Journal, 2010)
This book brings the greatest revolution of all -understanding the human brain. This will surely be a turning point in the history of human species for, unlike those earlier revolutions in science, this one is not about the outside world, not about cosmology or biology or physics, but about ourselves, about the very organ that made those earlier revolutions possible. The human brain, it has been said, is the most complexly organized structure in the universe and to appreciate this you just have to look at some numbers. The brain is made up of one hundred billion nerve cells or "neurons" which is the basic structural and functional units of the nervous system. Each neuron makes something like a thousand to ten thousand contacts with other neurons and these points of contact are called synapses where exchange of information occurs.
Keywords: human brain; revolutions; cosmology; biology; neurons